ACCESS TO DIGITAL CAR DATA AND COMPETITION IN AFTERMARKET MAINTENANCE SERVICES. (25th March 2020) - Martens, Bertin; Mueller-Langer, Frank
Abstract: Before the arrival of digital car data, car manufacturers had already partly foreclosed the maintenance market through franchising contracts with a network of exclusive official dealers. EU regulation endorsed this foreclosure but mandated access to maintenance data for independent service providers to keep competition in these markets. The arrival of digital car data upsets this balance because manufacturers can collect real-time maintenance data on their servers and send messages to drivers. These can be used to price discriminate and increase the market share of official dealers. There are at least four alternative technical gateways that could give independent service providers similar data access options. However, they suffer in various degrees from data portability issues, switching costs and weak network effects, and insufficient economies of scale and scope in data analytics. Multisided third-party consumer media platforms appear to be better placed to overcome these economic hurdles, provided that an operational real-time data portability regime could be established.